2017
DOI: 10.1111/resp.13170
|View full text |Cite
|
Sign up to set email alerts
|

Urinary desmosine is associated with emphysema severity and frequent exacerbation in patients with COPD

Abstract: This study indicates that the level of urinary desmosines measured by LC-MS/MS methods is associated with the CT emphysema index. Urinary desmosine can be a useful predictor in identifying frequent exacerbators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Not surprisingly, desmosine has been identified as a potential biomarker for structural lung injury in pulmonary TB and chronic obstructive pulmonary disease. 47,48 Overall, we propose that the metabolites here constitute a data subset indicative of alveolar destruction (Figure 2), progressive proteolysis, and establishment of lung fibrosis 49,50 occurring during TB progression.…”
Section: Tb Disease Progression Correlates With An Increase In Proteo...mentioning
confidence: 78%
“…Not surprisingly, desmosine has been identified as a potential biomarker for structural lung injury in pulmonary TB and chronic obstructive pulmonary disease. 47,48 Overall, we propose that the metabolites here constitute a data subset indicative of alveolar destruction (Figure 2), progressive proteolysis, and establishment of lung fibrosis 49,50 occurring during TB progression.…”
Section: Tb Disease Progression Correlates With An Increase In Proteo...mentioning
confidence: 78%
“…In the previous study, urinary desmosine was reported to be a useful biomarker for identifying frequent exacerbators of COPD patients. 52 Besides, the upregulation of IL-1 pathway mediators (IRAK2, IRAK3, PELI1 and IL1R1) 53 was reported to be relevant to frequent exacerbations of COPD. Fu et al 54 demonstrated that serum IL-6 and sputum IL-1β were associated with the frequent exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic arteries and the lung parenchyma may share high susceptibility to degradation of elastin and other components of the extracellular matrix [49]. In fact, desmosine, a specific biomarker of elastin degradation, has been associated with both emphysema and central arterial stiffness in COPD [50,51]. We cannot rule out the possibility that patients with mild COPD and greater emphysema burden were physically less active than their counterparts with less emphysema.…”
Section: Discussionmentioning
confidence: 93%